Integrasi Mitigasi Bencana Global Warming pada Materi Pembakaran Hidrokarbon melalui Pendekatan RBL-STEAM - Annida Nurul Shabrina; Bhakti Karyadi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
AbstractThe primary objective of this paper is to address the mitigation of disasters resulting from climate change and global warming. Such disasters are the result of increased greenhouse gas emissions, primarily caused by human activities like deforestation and the use of fossil fuels. To analyze the concept of hydrocarbon combustion from basic competencies (KD) 3.3 and 4.3 of chemistry class XI, we employed a qualitative descriptive method supported by a literature review. The paper investigates the relationship between climate change, the greenhouse effect, the carbon cycle, and their effects on the environment and health. Furthermore, it proposes a learning design that combines the Research-Based Learning (RBL) model with the STEAM approach to enhance students' comprehension of climate change, the consequences of hydrocarbon combustion, and emergency response measures. One of the highlighted learning strategies is the creation of an interactive and engaging mini park mockup to facilitate student understanding. The use of technology, specifically machine learning, is recommended for decision making in global warming disaster mitigation. This paper stresses the significance of integrating chemistry learning for knowledge and skills development in KD 3.3 and 4.3, and for understanding global warming and disaster mitigation efforts. The goal is to provide students with science literacy skills as well as the ability to identify concrete actions in reducing the negative impacts of climate change.